Enhancing mathematical proof skills in teacher education through etymology-based learning approaches - Rifat, Mohamad; Sudiansyah, Sudiansyah; Peterianus, Septian (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study aims to enhance students' understanding of mathematical proof through the etymology-based learning method. The research employs a descriptive approach to observe and analyze students' mathematical proof patterns in various contexts. Data were collected from 30 students enrolled in a master's degree program in mathematics education who demonstrated varying abilities in mathematical proof. The findings indicate that using action words or phrases during instruction can support students' ability to differentiate relevant terms and avoid misinterpretation of context. Furthermore, comparative understanding of source and target problems improves students' mathematical proof patterns in broader learning contexts. The implications of this study highlight the importance of integrating language-based and formal approaches in mathematics teaching to enhance students' mathematical proof abilities holistically.